What are they talking about? Pupil talk while translating Latin stories: a case study of a Year 7 class, using the Cambridge Latin Course - Rebecca Wright (The Journal of Classics Teaching, 2017)
The objective of this case study is to consider the role of pupil talk in the translation of Latin. I consider that ‘talk’ within the Latin classroom is an important pedagogical tool to support the development of pupil knowledge and understanding and to promote independent learning. Firstly, I am particularly interested in pupils’ early acquisition of the Latin language through ‘talk’. In this study, I wanted to explore how they use talk to support each other and the issues they encounter, the use of available and additional support resources and the extent of grammatical terminology within their talk. With the latter, I was curious to investigate how much terminology infiltrated pupils’ speech, or indeed if it was absent, and the subsequent effect both of these might have. The oral translation of Latin is an accepted and traditional part of learning for pupils. Throughout my PGCE teacher training course, I have observed that the majority of pupils frequently and independently consult or choose to work with another pupil when translating. I considered it was both a valid and valuable learning strategy to explore and analyse in some depth. Such research would provide a constructive insight into this accepted but sometimes overlooked learning tool, and therefore could realistically inform and improve my future teaching practice. Lastly, research into pupil talk has its own intrinsic worth, as transcripts provide both thought-provoking and informative evidence of their own. Thus, I was keen, within my placement school, to discover and consider how the pupils responded and talked about the language together in pairs.